Tumor intrinsic properties dictate Fc receptor expression and cancer cachexia associated increase in checkpoint inhibitor clearance - Remaily, Bryan C.; Young, Greg; Lathrop, Hannah; Thomas, Justin; Kim, Kyeongmin; Vu, Trang T.; Adeluola, Adeoluwa; Stanton, Camille; Mulcahy, Gillian; Xie, Zhiliang; Granchie, Lauren; Guo, Yizhen; et al. (Frontiers in Immunology, 2025)
PurposePatients with cancer cachexia display a general resistance to immune checkpoint inhibitor (ICI) therapy, and baseline ICI catabolic clearance is a predictive indicator for overall survival, independent of dose and drug exposure. Fc-gamma (FcγRs) and neonatal Fc receptors (FcRn) play key roles in ICI clearance and efficacy, and we aimed to determine the impact of cachexia, independent of tumor, on immune cell populations and their Fc receptor (FcR) expression in patients and in murine models of cancer, cachexia, and cancer cachexia.Experimental designImmune cell populations and their FcR expression were measured in tumor-bearing and tumor-free mice, with/without cachexia, and from patients with non-small cell lung cancer (NSCLC) and renal cell carcinoma. These measures, upon splenocytes and peripheral blood mononuclear cells (PBMCs) in mice and humans respectively, were compared with baseline ICI drug clearance and cachexia phenotype.ResultsLeukocyte populations and FcγR in mouse splenocytes displayed distinct expressional patterns when comparing across tumor and cachexia status. Univariate analyses revealed several correlations between FcγR expression on patient PBMCs and both ICI clearance and cachexia phenotype. Notably, FcRn expression was unchanged or slightly elevated in tumor-bearing mice and did not correlate with ICI clearance in murine splenocytes or patient leukocytes. Furthermore, immune cell populations and FcR expression were different among tumor types but did not differ in splenocytes of tumor-free mice with Activin A/IL-6 induced cachexia when compared with vector controls.ConclusionsThese findings provide the first evidence that FcRs, critical for the efficacy and pharmacokinetics of many ICI and other IgG mAbs, are altered in a tumor-dependent manner. Furthermore, in the absence of a tumor, cachexia phenotype may not coincide with inflammation in the form of altered immune cell populations and elevated catabolic clearance of IgG mAbs, suggesting these features arise from properties intrinsic to the tumor.